Asymmetric Election: Political Decentralization As A Lesson Learnt From Indonesia 2019 Simultaneous Election Problems - Adi Suryanto; Nurliah Nurdin; Sukhumvit Saiyasopon; Ahmad Martadha Mohamed; Aqil Teguh Fathoni (Universitas Muhammadiyah Yogyakarta, 2021)
Asymmetric election has been discussed as alternative for Indonesia model of election considering the massive problems of current simultaneous election. Having large population, huge number of voters, disparities of islands geographic obstacles along with strong decentralization of government endorsement then political decentralization must run side by side to support each other for social accountability and public services. Starfish concept of decentralization model could be best describing the necessity of having asymmetric election where local voices matters. All politics is local is an important issue in the national level where the way of electoral system must be coherent. The paper argues that election at the national level must be separated from DPR and DPD and Presidential election alone to put respect at the national leader as well as a call for public attention in their candidacy. Focusing on Presidential election alone ignoring DPR, DPD and DPRD only result not only degradation of democracy but also morality. At the local level should be held an election for DPRD member and Head of Region election. This could emphasis local issue where local people need to think and put more attention on their representatives who going to voice their interests on local regulations.